The future of sex in elite sport - Photopoulos, J. (Nature, 2021)
In the excitement of leaving for the 1985 World University Games in Kobe, Japan, Spanish hurdler María José Martínez-Patiño forgot to pack her doctor-issued `certificate of femininity`. "You had to prove you were a woman in order to compete," she explains. Without it, she had to take a simple biological test. But it produced an unexpected result, and so she had to take a more thorough test — one that would take months to process. The team physician advised her to fake an ankle injury to silence suspicion around why she was not running, so she sat in the stands with her foot bandaged and watched, wondering what the test result meant. Sport has a long history of policing who counts as a woman. Blanket mandatory `sex verification` testing was put in place at events in the 1960s (see `Policing sex`) — a time when women`s participation in sport was on the rise and many were making huge performance improvements. Concerns that men might be masquerading as women forced people competing in women`s events to undergo a demeaning visual and physical examination by a panel of doctors. In 1968, the International Olympic Committee (IOC) adopted a different test to determine sex, based on chromosomes. People usually have 46 chromosomes arranged in 23 pairs. One of these pairs differs depending on the biological sex of the individual: women typically have two X chromosomes, whereas men typically have an X and a Y. Genetic errors, mutations and interactions between DNA and hormones can, however, cause a panoply of exceptions to this arrangement. Although a person`s chromosomes might indicate one sex, their anatomy might suggest otherwise. This is known as intersex or differences of sex development (DSDs). The chromosome-based test required by the IOC involved taking cells from inside the cheek. In a cell containing two X chromosomes, one chromosome is inactive and therefore shows up under the microscope as a dark spot in the nucleus, known as a Barr body. If the dark spot was not clearly identifiable, the result could then be checked by cataloguing the chromosomes present in a cell.